1996
DOI: 10.1046/j.1537-2995.1996.36111297091738.x
|View full text |Cite
|
Sign up to set email alerts
|

Time‐dependent, spontaneous release of white cell‐ and platelet‐derived bioactive substances from stored human blood

Abstract: Stored whole blood, plasma-reduced whole blood, and saline-adenine-glucose-mannitol blood may release white cell- and platelet-derived bioactive substances in a time-dependent manner, which may be related to the detrimental effects of perioperative blood transfusions. Therefore, prestorage white cell reduction should be considered for further improvement of red cell suspensions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
129
3
5

Year Published

2001
2001
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(143 citation statements)
references
References 39 publications
6
129
3
5
Order By: Relevance
“…Potential causes of delayed morbidity include acute lung injury, 6,7 infection, [8][9][10] and multiple organ failure 10,11 mediated by pro-inflammatory effects of leukocytes. 29 We found several other noteworthy associations. First, later year of hospital admission was associated with higher 48-hr mortality.…”
Section: Discussionmentioning
confidence: 58%
“…Potential causes of delayed morbidity include acute lung injury, 6,7 infection, [8][9][10] and multiple organ failure 10,11 mediated by pro-inflammatory effects of leukocytes. 29 We found several other noteworthy associations. First, later year of hospital admission was associated with higher 48-hr mortality.…”
Section: Discussionmentioning
confidence: 58%
“…These mediators are contained in intracellular WBC granules, and are released in a time-dependent manner as the WBCs deteriorate during storage [59]. It has been shown that at least some of these biologic response modifiers (histamine, eosinophil cationic protein, eosinophil protein X, TGF-β) may contribute to the development of immunosuppression and tissue damage by inhibition of neutrophils, cytotoxic T-cells and natural killer cells [60], [61], [62], [63].…”
Section: Immunosuppressionmentioning
confidence: 99%
“…The average WBC content of transfused WBCreduced RBCs was less than 5 ϫ 10 6 per unit, and was often as low as 1 ϫ 10 6 per unit. The timing of the filtration procedure is important because biologic response modifiers released from WBC granules in a time-dependent manner during storage may mediate the adverse TRIM effects, 39,48,[56][57][58][59][60] and-if such TRIM effects really exist-only WBC-reduced RBCs filtered before storage can be expected to abrogate the adverse effects. Two RCTs administered autologous RBCs 4 or whole blood 23 to the control arm.…”
Section: Design Of Clinical Studiesmentioning
confidence: 99%